Nutritional Status of Heart Failure Outpatients: Food, function and feelings - Vilborg Kolbrún Vilmundardóttir 1990- (2017)
Malnutrition is associated with increased length of stay in hospital and further complications, consequentially increasing the cost of care. Heart failure is a disease prevalent in older adults, characterized by chronic symptoms, such as fluid retention, dyspnea and fatigue. Therefore patients suffering from heart failure are a delicate group that can be susceptible to malnutrition. Evaluation of nutritional status has never been performed for this group in Iceland. Aim: To assess the risk of malnutrition in heart failure outpatients using the Simple Screening Tool for Malnutrition (SSM) as well as assessing the nutritional status of a smaller sample of the same population using estimations of: appetite and dietary intake; body mass index, reported weight loss and fluid retention; biochemical measurements; grip strength and quality of life. Methods: This was a cross-sectional study. All patients with an appointment at the outpatient clinic of heart failure at Landspítali University Hospital (department 14F) were screened for malnutrition (n=84). A total of 60 patients were invited to participate, whereof 33 signed an informed consent (55%). Participation consisted of answering three questionnaires, as well as undergoing blood sampling and measurement of grip strength. Information on the results of SSM, ICD-10 diagnoses, medication, height, weight, blood pressure and edema were collected from electronic medical records. Results: Screening for all patients showed (n=84) that around 30% (n=25) were at medium or severe risk of malnutrition. Participants (n=33) were of both sexes, thereof 27% (n=9) women and medium age was 76 (25th, 75th percentiles; 70, 80) years. The participants’ diet turned out to be rather rich in protein, with majority reporting to eat at least one warm meal per day. A total of 23% of participants reported to have felt loss of appetite and 27% (n=9) reached reference values for grip strength. Mean T-score for quality of life was 43.8 (±10.4), with the norm being 50±10. In total, 19% (n=6) of ...